Reflecting on the Potential and Limitations of Urban Agriculture as an Urban Greening Tool in South Africa - Cilliers, Elizelle Juanee; Lategan, Louis; Cilliers, Sarel Stephanus; Stander, Karla (Frontiers in Sustainable Cities, 2020)
Urban green spaces have been researched extensively for their contribution towards livable, sustainable and resilient cities. Studies illustrate increasing awareness of the multi-functional roles such spaces can fulfill in addressing urbanization pressures and associated impacts such as increasing stress on global food systems, notably by accommodating practices of urban agriculture (UA). This paper investigates the potential for UA in South Africa as a citizen-led urban greening strategy, considering potential and limitations for the increased application of UA in spatial planning. The paper provides a review of core concepts and illustrates potential and certain limitations via UA cases studies in two leading South African provinces and a review of the national policy and legislative framework pertaining to UA. Findings highlight particular issues for consideration to augment the implementation of UA in South Africa, including opportunities to draw on existing citizen-led initiatives and increasing awareness of UA among communities, authorities, non-governmental organizations and the private sector; the potential to utilize skilled and knowledgeable rural migrants; and possibilities to capitalize on a growing market for UA related opportunities to stimulate economic growth and employment creation whilst addressing food security concerns. Limitations highlighted in the paper, include many current UA initiatives not being self-sustaining and fully citizen-driven, requiring constant support and resources from multiple stakeholders; a cultural stigma attached to UA activities, hampering more uptake, especially among the youth; limited national support as no dedicated national policy on UA exists to direct the spatial planning community; and lastly, that South African spatial planners exhibit limited knowledge of UA and green infrastructure in general. The paper concludes with broad recommendations for the international planning community to advance the implementation of UA as a citizen-led urban greening strategy, drawing on the South African experience.